TARGET PERTUMBUHAN INVESTASI DAN RENCANA STRATEGI PENGEMBANGAN INVESTASI PROVINSI PAPUA - Marsi Adi Purwadi; Yundy Hafizrianda; Ida Ayu Purba Riani (KEUDA (Jurnal Kajian Ekonomi dan Keuangan Daerah), 2018)
In general intent and purpose of this study is to give an overview of investment policy direction in Papua province in relation to improving the economic growth both sectoral and regional basis. Some quantitative methods used are macroregional regional development planning models such as growth models, COR and ICOR. The required data is covered by a documentation method sourced from a competent agency. Where the results of this study indicate that: 1) It is seen that spatially, out of the 29 districts or cities the ICOR has been calculated, there are 20 regions considered to have low cost to investment because they have a low ICOR; 2) Based on the ICOR analysis, it was found that during the period of 2012-2016 the most inefficient economic sector in Papua Province was the industrial sector; 3) Referring to the very low ICOR magnitude with an average below 4, it is finally generalized that efforts to increase regional investment in Papua Province in the future should be directed to agriculture-based sectors. Keywords : Investment, ICOR, Economic Growth